Ethanol and Protein from Ethanol Plant By-Products Using Edible Fungi Neurospora intermedia and Aspergillus oryzae - Bátori, Veronika (Hindawi Publishing Corporation, 2015)

(untitled) (Biomed Res Int)
Feasible biorefineries for production of second-generation ethanol are difficult to establish due to the process complexity. An alternative is to partially include the process in the first-generation plants. Whole stillage, a by-product from dry-mill ethanol processes from grains, is mostly composed of undegraded bran and lignocelluloses can be used as a potential substrate for production of ethanol and feed proteins. Ethanol production and the proteins from the stillage were investigated using the edible fungi Neurospora intermedia and Aspergillus oryzae, respectively. N. intermedia produced 4.7 g/L ethanol from the stillage and increased to 8.7 g/L by adding 1 FPU of cellulase/g suspended solids. Saccharomyces cerevisiae produced 0.4 and 5.1 g/L ethanol, respectively. Under a two-stage cultivation with both fungi, up to 7.6 g/L of ethanol and 5.8 g/L of biomass containing 42% (w/w) crude protein were obtained. Both fungi degraded complex substrates including arabinan, glucan, mannan, and xylan where reductions of 91, 73, 38, and 89% (w/v) were achieved, respectively. The inclusion of the current process can lead to the production of 44,000 m(3) of ethanol (22% improvement), around 12,000 tons of protein-rich biomass for animal feed, and energy savings considering a typical facility producing 200,000 m(3) ethanol/year.